An analysis of the load-bearing capacity of timber-concrete composite beams with profiled sheeting = Analiza nośności belek zespolonych drewniano-betonowych z płytą betonową na blasze fałdowej - Szumigała, Maciej; Szumigała, Ewa; Polus, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents an analysis of timber-concrete composite beams. Said composite beams consist of rectangular timber beams and concrete slabs poured into the steel sheeting. The concrete slab is connected with the timber beam using special shear connectors. The authors of this article are trying to patent these connectors.
Keywords: composite structures; constructions aluminium-timber; composite beams; FEM; ABAQUS; struktury kompozytowe; konstrukcja aluminiowo-drewniana; belka zespolona; MES